Variability in the diving activity of Antarctic fur seals, Arctocephalus gazella, at Iles Kerguelen - Mary-Anne Lea; Mark Hindell; Guinet, C; Goldsworthy, SD (2002)
Intra-population variation in diving behaviour of lactating Antarctic fur seals (Arctocephalus gazella) was studied at the Kerguelen Archipelago (49°07′S, 70°45′E) during the austral summers of 1998-2000. Dive data were successfully recorded for 112 seals equipped with time-depth recorders during 117 foraging trips. All seals displayed bouts of diving activity and the nocturnal foraging behaviour typical of otariids preying on pelagic fish and squid. Mean dive depth (53 m) was considerably deeper than recorded for this species at other sites. Four diving behaviour groups were identified: (1) deep divers (n = 60); (2) shallow-active divers (n = 45); (3) shallow divers (n = 9); (4) daytime divers (n = 3). The distribution of trips assigned to the various behavioural dive groups varied significantly between years. Antarctic fur seals at Kerguelen exhibit flexible diving strategies both within and between populations in response to changes in environmental conditions and prey availability. Electronic supplementary material to this paper can be obtained by using the Springer Link server located at http://dx.doi.org/10.1007/s00300-001-0339-6.